Ethics Audits in Cross-National Research: Experiences from Correspondence Study Field Experiments with National Politicians in Four European Democracies. (May 2022) - Pedersen, Helene Helboe; Louwerse, Tom; Zittel, Thomas
This essay contemplates experiences from four national ethics audits designed to facilitate correspondence study field experiments with national politicians in Germany, the Netherlands, Denmark and the United Kingdom. The experimental study aims to reveal possible biases in legislators' responsiveness to distinct types of constituents such as non-partisans, lower-class constituents, ethnic minorities, and women, and to unveil possible unsubstantiated fears or misperceptions in this regard. The national research teams proposed the same experimental design but received three different ethical evaluations. Specifically, the relevant Institutional Review Boards (IRBs) in the UK and Denmark asked for two different de-briefing procedures. In the Danish case, this led to withdrawal of the experiment due to severe costs with regard to research quality. In the UK case, it led to increased risk of backlash. Our experiences imply a need for more consistent ethics regimes in the European research community designed to facilitate comparative social science research.